Analysis of Key Barriers to theUse of the Internet of Things in Iranian Smart Cities (Structural Analysis Method) - Azadeh Fallahi; amin faraji; amin gharibi (مطالعات مدیریت کسب و کار هوشمند, 2021)
Today, many countries are institutionalizing the concept of smart city and implementing IoT programs that support smart city components, relying on the extensive IT infrastructure to improve the sustainability and quality of life needed by their communities. But using the Internet of Things to develop a smart city faces several challenges. Accordingly, the purpose of this study is to identify the main challenges of the Internet of Things and to understand the relationship between these challenges to support the development of smart cities in Iran. Initially, 14 major challenges were extracted based on domestic and foreign literature. Then, using the SWARA technique, the challenges were prioritized based on summarizing the views of seven relevant experts in the field of smart cities in Iran. In the next step, the underlying interactions between the identification challenges and their importance were determined using interpretive structural modeling (ISM). Then, MICMAC method was used to confirm the results. According to the findings, the challenges in the interpretive structural method were leveled at six levels. Then, to test the results of this stage, MICMAC method was used.The results of this stage showed that the lack of policies, perspectives and regulatory guidelines, high training, operational and maintenance costs, inequality (social), lack of transparency and responsibility, lack of technical knowledge among Planners, lack of technology infrastructure and lack of intelligence were identified as influential and key variables of the study.